ANALISIS PENGARUH PAJAK PARKIR, PAJAK RESTORAN DAN RETRIBUSI PARKIR TERHADAP PENDAPATAN ASLI DAERAH KOTA MALANG (Studi Kasus Badan Pengelola Keuangan dan Aset Daerah Kota Malang) - Asma Mufidah; Jeni Susyanti; Afi Rachmat S (UNIVERSITAS ISLAM MALANG, 2017)
The purpose of this research are: 1) To analyze the effect of parking tax toward Regional Original Income of Malang, 2) To analyze the effect of restaurant tax toward Regional Original Income of Malang, 3) To analyze the effect parking retribution toward Regional Original Income of Malang. Subjects of this study are The Original Realization Report of Regional Original Income which derived from parking tax, restaurant tax and parking fees on 2011 - 2015, data source are secondary data obtained from records or reports receipts that have been arranged in the archive (documentary data) which is acquired from Financial Management Agency and Asset of Malang. This study uses a quantitative approach, assorted explanatory research. The results showed that the Parking Tax, Restaurant Tax, and Parking Retribution partially have significant influence toward Regional Original Income of Malang